Effectiveness of Solar System Scope-Assisted PBL on Kepler Law Material Integrated with Al-Quran to Improve Student Learning Outcomes - Khairiah Khairiah; Hajar Mawaddah; Lia Afriyanti Nasution; Ahmad Fudholi; Mohd Awang Kechik; M. Khadafi Somwong (Postgraduate, University of Mataram, 2024)
This research is motivated by the low ability of students to understand physics subjects which are considered difficult, including the difficulties experienced namely visualizing subject matter which requires learning models and media as support to improve student learning outcomes. This research was conducted at MA Muallimin UNIVA Medan, by applying the Problem Based Learning (PBL) learning model assisted by Solar System Scope media on Kepler law material integrated with the Koran which is used in the learning process to improve student learning outcomes. The research method used is experimentation which is a type of quantitative research in class X MIA 1 as an experimental class with a Probe Based Learning (PBL) learning model. The sample was taken using a purposive sampling technique. The instrument used is a written test (essay) with 10 questions. It is known that the pretest and posttest data are normally distributed with a significance value of Experimental Pretest (0.078), Experimental Posttest (0.130), Control Pretest (0.200), Control Posttest (0.052) and are declared homogeneous with a significance value of Based on Mean (0.245) where the test value normality and homogeneity exceed (>) the real level used in the measurement, namely α = 0.05 or 5%. With the help of SPSS it is known that the average learning outcomes of students in the experimental class (83.07) are higher than those in the control class (79.90) so it can be concluded that the hypothesis is accepted and the average of the experimental class is stated to be better than the average of the control class. As for the effectiveness of the experimental class with the PBL (Problem Based learning) model, it was 76.6% and the control class with the Direct Instruction learning model was 54.4%, where the experimental class was declared effective and the control class was declared less effective.